C-reactive protein: An inflammatory biomarker in oral cancer - Ashwini Kumar Mengji; Uday Shankar Yaga; Radhika Besta; Swetha Soankamble (Wolters Kluwer Medknow Publications, 2015)
C-reactive protein (CRP) is a plasma phase protein that takes part in systemic responses to inflammatory reactions. Its serum concentration can increase up to 1000 folds or more in relation to acute stimuli due to infections, tissue injuries, and malignant disorders. It is highly resistant to proteolysis, principally synthesized in the liver in response to proinflammatory cytokines, i.e. interleukin (IL)-6, IL-1β, and tumor necrosis factor. These cytokines are seen to be related to neoplastic disorders. It forms an integral component of innate immunity and serves primarily to recognize potential pathogens and damaged cells. The present article summarizes the importance of CRP and its significance in oral cancer and associated disorders. It was found that a lowered CRP level may prove to be beneficial in prevention and treatment of oral cavity cancer.